Understanding opportunity focus and its effects on douala micro-small enterprises sales performance - Angelus, Efeutlancha Forji; Aloysius, Njong Mom; Felix, Nkiendem (goodwood publishing, 2025)
Purpose: The main purpose of this study is to understand opportunity focus and its effects on the sales performance of micro-small enterprises in Douala. Research Methodology: This study adopted a quantitative research design using a questionnaire as the primary data collection instrument. The sample size of 385 was determined using the Cochran formula for an unknown population and selected using simple random sampling. The collected data were analyzed using the ordinary least squares technique (OLS) with the help of STATA 17. Results: The findings revealed a positive and significant effect of opportunity focus on sales performance in micro- and small-sized enterprises in Douala V, Cameroon. The results also show that younger business owners outperform their older counterparts in terms of sales performance. Conclusions: This study provides insightful policy recommendations for micro and small businesses, newly formed NGOs, governments, and other stakeholders to bolster their competitive positions, contribute to sustainable and inclusive economic growth, and foster innovation and entrepreneurship in their sectors. Limitations: The study is limited to micro and small-sized enterprises in the Douala Five municipality, making generation difficult for other medium and large enterprises within and out of the Douala Five municipality since these enterprises vary in size and definitely differ in resource constraints Contribution: This study provides insightful policy recommendations for micro and small businesses, newly formed NGOs, governments, and other stakeholders to bolster their competitive positions, contribute to sustainable and inclusive economic growth, and foster innovation and entrepreneurship in their sectors.